A Double Dwell Frequency Synchronization Scheme For OFDM Systems - Kousa, Nour Ali (2015)
A Master of Science thesis in Electrical Engineering by Nour Ali Kousa entitled, "A Double Dwell Frequency Synchronization Scheme For OFDM Systems," submitted in January 2015. Thesis advisor is Dr. Mohamed El-Tarhuni. Available are both soft and hard copies of the thesis.